PROSPECTS FOR OVERCOMING GLOBAL CHALLENGES OF THE XXI CENTURY IN A POSTMODERN REALITY - Kleshnia, Hanna (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Introduction. The idea of implementing a synergistic methodology and giving society the "freedom" of self-organization and self-regulation in order to "manage chaos" showed its inability in the ХХІ century. Upheaval at the end of the ХХ c. they look like skillfully constructed chaos that, through reforms, replaced state technocracy with a global one. Such "social reformation" coincided in time with a sharp aggravation of global problems actualized in the last century. The aim is to study the influence of modern approaches of technocratism and synergetic on the assessment of the social transformations that have taken place, and the analysis of strategies and projects for countering global risks, which humanity seeks to implement in the XXI century. Research methodology is philosophical principles of objectivity, reflection, development and interconnection. The dialectical method of knowing reality in its contradictions, integrity and development is applied. The system approach reflects the self-organization and structuring of systems as a universal quality of society. Research results. The world of the XXI c. demonstrates the trends that, in fact, do not correspond to predefined and deterministic technocratic approaches. For their explanation, it is appropriate to use the concept of non-linear development, widespread in scientific discourse. Indeed, with the emergence of theories of probability, nonlinearity and synergy in modern post-classical science, a nonlinear understanding of development begins. In essence, the classical understanding of development is based on the desire to order the world and tame chaos, while the non-classical one is based on the artificial creation of entropy and the attempt to control chaos. However, specific examples also confirm the fact that even in conditions of artificially created chaos, management methods remain old - traditionally technocratic in their worst version. Discussion. In philosophical thought, the concept of technocracy is one of the options for the vision of the future of humanity. In the XXI c. it has undergone several changes, approaching the concepts of local civilizations, culture and post-industrial society in different ways, but it has retained its position among the projects and forecasts of human development. Technocrats and technocracy are usually contrasted with the "humanistic renaissance" of modern philosophy in modern social and philosophical thought. Conclusions. In the conditions of the "turned inside out" world, it is quite natural that global problems cannot be overcome by traditional means and proven methods. So, foremost, the global world system needs revision. Only by taming the artificially created controlled chaos, it will be possible to carry out creative plans to save the world.